Light-Driven Chiral Molecular Switches or Motors in Liquid Crystals - Wang, Yan; Li, Quan (Advanced materials (Weinheim), 2012)
The ability to tune molecular self‐organization with an external stimulus is a main driving force in the bottom‐up nanofabrication of molecular devices. Light‐driven chiral molecular switches or motors in liquid crystals that are capable of self‐organizing into optically tunable helical superstructures undoubtedly represent a striking example, owing to their unique property of selective light reflection and which may lead to applications in the future. In this review, we focus on different classes of light‐driven chiral molecular switches or motors in liquid crystal media for the induction and manipulation of photoresponsive cholesteric liquid crystal systems and their consequent applications. Moreover, the change of helical twisting powers of chiral dopants and their capability of helix inversion in the induced cholesteric phases are highlighted and discussed in the light of their molecular geometric changes. The ability to tune molecular self‐organization with an external stimulus is a main driving force in the bottom‐up nanofabrication of molecular devices. Light‐driven chiral molecular switches or motors in liquid crystals that are capable of self‐organizing into optically tunable helical superstructures undoubtedly represent such a striking example. In this review, we focus on different classes of light‐driven chiral molecular switches or motors in liquid crystal media for the induction and manipulation of photoresponsive cholesteric LC systems and their consequent applications.